US public support for vaccine donation to poorer countries in the 2009 H1N1 pandemic. - Supriya Kumar (Public Library of Science (PLoS), 2012)
Background During the 2009 H1N1 pandemic, the global health community sought to make vaccine available "in developing nations in the same timeframe as developed nations." However, richer nations placed advance orders with manufacturers, leaving poorer nations dependent on the quantity and timing of vaccine donations by manufacturers and rich nations. Knowledge of public support for timely donations could be important to policy makers during the next pandemic. We explored what the United States (US) public believes about vaccine donation by its country to poorer countries. Methods and findings We surveyed 2079 US adults between January 22(nd) and February 1(st) 2010 about their beliefs regarding vaccine donation to poorer countries. Income (p = 0.014), objective priority status (p = 0.005), nativity, party affiliation, and political ideology (p<0.001) were significantly related to views on the amount of vaccine to be donated. Though party affiliation and political ideology were related to willingness to donate vaccine (p<0.001), there was bipartisan support for timely donations of 10% of the US vaccine supply so that those "at risk in poorer countries can get the vaccine at the same time" as those at risk in the US. Conclusions We suggest that the US and other developed nations would do well to bolster support with education and public discussion on this issue prior to an emerging pandemic when emotional reactions could potentially influence support for donation. We conclude that given our evidence for bipartisan support for timely donations, it may be necessary to design multiple arguments, from utilitarian to moral, to strengthen public and policy makers' support for donations.